Knowledge, Attitude, and Behavior of Parents Regarding Early Childhood Caries Prevention of Preschool Children in Western Region of Saudi Arabia: A Cross-Sectional Study - Afnan A. Nassar; Buthaina A. Fatani; Othoob T. Almobarak; Shahad I. Alotaibi; Reem A. Alhazmi; Abdullah A. Marghalani (MDPI AG, 2022)
The knowledge and beliefs of parents have an impact on their children's general and oral health. The objective of this study is to assess knowledge, attitude, and behavior of parents and identify possible associated factors of early childhood caries (ECC) in the western region of Saudi Arabia. Parents aged 18 and older were invited to complete a self-administered, validated questionnaire. Questions covered demographics, knowledge, attitude, and behavior regarding ECC etiology and prevention. Of the 644 parents who completed the questionnaire, 51.4% were not aware of the early signs of tooth decay, such as white lines. Pain and trauma were reported as the major reasons for a child to visit a dentist (42.4%). Only 37% of parents were aware of the importance of fissure sealant, and only 23% knew how it is applied. Compared with mothers, fathers were significantly less aware of hidden sugar and the relation between the frequency of consuming breast milk or bottled milk and caries development (p = 0.001). Similarly, fathers were more likely to believe that children could achieve effective teeth cleaning without parental assistance (p = 0.001). Preventive guidance should be provided by oral healthcare providers in Saudi Arabia to improve parents' knowledge of ECC prevention.